2020
DOI: 10.1016/j.ypmed.2020.106047
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and public health burden of sunburn among beachgoers in the United States

Abstract: The beach environment creates many barriers to effective sun protection, putting beachgoers at risk for sunburn, a well-established risk factor for skin cancer. Our objective was to estimate incidence of sunburn among beachgoers and evaluate the relationship between sunburn incidence and sun-protective behaviors. A secondary analysis, of prospective cohorts at 12 locations within the U.S. from 2003 to 2009 (n = 75,614), were pooled to evaluate sunburn incidence 10-12 days after the beach visit. Behavioral and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In addition, a more prominent sun tanning and beach culture seemed to be present in NS/PEI, and participants from this group, along with those from NB, described more experiences with sunburns. This is consistent with the findings of a large US-based prospective cohort study (n = 75,614), in which 13.1% of beachgoers reported sunburn, with the highest sunburn rates occurring at beaches along the Eastern Seaboard [37], an area that is geographically proximate to Atlantic Canada.…”
Section: Microsystem: Sun Protection Habitssupporting
confidence: 90%
“…In addition, a more prominent sun tanning and beach culture seemed to be present in NS/PEI, and participants from this group, along with those from NB, described more experiences with sunburns. This is consistent with the findings of a large US-based prospective cohort study (n = 75,614), in which 13.1% of beachgoers reported sunburn, with the highest sunburn rates occurring at beaches along the Eastern Seaboard [37], an area that is geographically proximate to Atlantic Canada.…”
Section: Microsystem: Sun Protection Habitssupporting
confidence: 90%
“…However, another study conducted in a sample of beach handball players from Spain found a higher sunburn frequency (76.9% had at least one sunburn in the last year) ( De Castro-Maqueda et al, 2019 ). These sunburn events could be related to prolonged sun exposure among the populations mentioned, in addition to insufficient sun protection measures ( DeFlorio-Barker et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 Although beach destinations generally offer pleasurable climatic conditions, they are normally associated with a high-solar ultraviolet radiation (UV) environment, 2 especially at latitudes below 40°. A consequence of a high-solar environment is a heightened risk of overexposure, which manifests itself not only in an elevated risk of sunburn [3][4][5] but also to DNA damage in the skin. 6 Furthermore, the acute high-UV exposure often received on a beach holiday contributes significantly to our annual cumulative UV exposure, making recreational exposure in a high-solar environment an important contributor to lifetime risk of skin cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although beach destinations generally offer pleasurable climatic conditions, they are normally associated with a high‐solar ultraviolet radiation (UV) environment, 2 especially at latitudes below 40°. A consequence of a high‐solar environment is a heightened risk of overexposure, which manifests itself not only in an elevated risk of sunburn 3–5 but also to DNA damage in the skin 6 …”
Section: Introductionmentioning
confidence: 99%